Frontline Workers in the Backrooms of COVID-19: Caring for the Living and the Dead. Issue 3 (17th June 2020) - Myers, Jeffrey L; Mulder, Lotte
Abstract: Objectives: To review the response to the coronavirus disease 2019 (COVID-19) pandemic in a forensics center that integrates an academic department of pathology with multiple regional county medical examiners' offices. Methods: Faculty and staff were asked to volunteer stories, data, and photographs describing their activities from March through May 2020. The information was assembled into a narrative summary. Results: Increased deaths challenged capacity limits in a hospital morgue and a large urban medical examiner's office (MEO) successfully managed by forensic teams and monitored by an institutional command center. Autopsies of suspected and proven cases of COVID-19 were performed in both facilities. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing of decedents was performed in a MEO serving a large urban area. Scene investigators worked directly with families to meet needs unique to a pandemic. Artful photographs of decedent's hands and/or tattoos were offered to those unable to have in-person viewings. Pathologists and social workers were available to families of the deceased and created novel solutions to facilitate the grieving process. Conclusions: Forensic pathology is important to successfully navigating emerging diseases like the COVID-19 pandemic. Direct conversations with families are common in forensic pathology and serve as a model for patient- and family-centered care.